FAKTOR KEBUDAYAAN DALAM PENENTUAN POSITIONING - Yuliadewi, Lesie (Nirmana, 1999)
The culture is the important part to influent people s attitudes like the way they have seen or thinked. Usually%2C people will learn some thing faster than the other%2C because it has been related with their past experience. That is why%2C the culture become one of the most important thing in advertising and it have great influence for the brand image of the consumers. So the consumers can be easily remember the products that have been advertising. Last%2C all of it%2C will change the sales of the products goes up and hopefully%2C it will increase the revenue/profit of the firm. Abstract in Bahasa Indonesia : Kebudayaan akan mempengaruhi sudut pandang seseorang terhadap sesuatu yang dilihat atau diterima oleh otaknya. Seseorang akan lebih cepat menerima sesuatu apabila ciri-ciri hal yang baru diterimanya berhubungan dengan masa lampaunya. Oleh karena itu%2C kebudayaan merupakan faktor yang penting diperhitungkan agar pesan yang termuat dalam iklan cepat diterima dan diingat di benak calon konsumen%2C sehingga angka penjualan dapat meningkat.